Fe/CeO2 Catalysts for Highly Efficient Degradation of Congo Red at Low Temperature - Hu, Cheng (Asian Journal of Chemistry, 2014)
Fe/CeO2 catalysts were prepared by combining with sol-gel and impregnation method. The structures of catalysts were characterized by X-ray diffraction. The results showed that the addition of Fe into CeO2 unaffected the crystalline structure of CeO2 and Fe emerged highly dispersed state. In the range of 5-35 °C, the 2 wt. % Fe/CeO2 catalyst towards 10 mgL-1 azo dyes Congo Red by catalytic wet hydrogen peroxide oxidation (CWPO) displayed highly catalytic activity. Furthermore, at room temperature (25 °C), the degradation percentage of Congo Red was 96 % with the amount of 0.05 g catalyst and 0.02 M H2O2 (30 wt. %) after reacting 40 min. At the same time, the repetitive experimental results of catalyst have shown that the catalyst had excellent stability.